25 years of relationship research in sport: The quality of the coach-athlete relationship as defined by Closeness, Commitment, Complementarity and Co-orientation (3+1Cs Model) - Jowett, S. (Psychology of Sport and Exercise, 2025)
Abstract The value of the coach-athlete relationship is important because its quality offers the context within which sport participation and performance can become a truly positive experience - an experience that both coaches and athletes remember fondly for years to come. There are many examples of high-profile athletes who reflect on their coach-athlete relationships as forces for good, creating a significant positive impact on their development as athletes and as human beings. For example, Michael Phelps, Tom Daley, Serena Williams, Michael Johnson, Bryony Page, and Cristiano Ronaldo to mention a few, have referred to the strong partnerships they developed with their coaches, the importance of connection and its transformative long-term effect. In this paper, I focus on the phenomenon of the coach-athlete relationship not as an idea but as a reality and as a research area that has made significant strides over the past 25 years. Guided by theoretical and empirical evidence, I highlight that relationships between coaches and athletes provide a significant avenue to better coaching and to a more wholesome sport experience that is based on partnership and dialogue leading to lasting personal and interpersonal fulfilment even well beyond the confines of sport.